Powerstarts
PowerStarts® has developed a start-dive technique that will take time off of almost any swimmer's races. The PowerStarts® Start-Dive Training SystemTM takes maximum advantage of physics, biomechanics, kinesiology, ballistics, and hydrodynamics, yet is taught in a fun and simple manner such that the swimmer need not understand any of the "-ics" and "-ologies" to enjoy the full benefit of the techniques.